FORMULATION AND EVALUATION OF ORMELOXIFENE FAST DISSOLVING TABLETS - Sathali, Abdul Hasan; M, Ramanathan (Asian Journal of Pharmaceutical Research and Development, 2018)
The objective of the present work was to enhancedissolution and solubility of slightly water soluble ormeloxifene hydrochloride and formulate fast dissolving tablets. The research work was two-phase process, the first phase was to enhance the solubility and dissolution of ormeloxifene. For this object drugwas processed with different solid dispersion techniques like kneading, co precipitation, melting and solvent evaporation technique with